An analysis of Social StoriesTM research using an evidence‐based practice model. Issue 3 (5th September 2012) - Mayton, Michael R.; Menendez, Anthony L.; Wheeler, John J.; Carter, Stacy L.; Chitiyo, Morgan
<x xml:space="preserve">Abstract</x> The number of Social StoriesTM studies and reviews has increased in recent years, yet concerns regarding quality and effect sizes continue to be expressed. With the emphasis on evidence‐based practices (EBPs) for the education and treatment of people with autism spectrum disorders (ASD), this issue becomes of paramount importance as professionals and parents attempt to select interventions for the people with ASD in their care. The current study makes a unique contribution in its use of an extensive EBP evaluation model to examine 33 single‐subject studies across 13 peer‐reviewed journals, a 12‐year period, and a wide range of grouping variables. Using the Mayton, Wheeler, Menendez and Zhang (2010) EBP evaluation protocol, studies were investigated in terms of eight quality indicators comprised 23 operationally defined standards. Studies included in this analysis met the following criteria: (1) they were intervention studies using single‐subject research designs; (2) they included only participants with disorders on the autism spectrum; and (3) the primary intervention was the use of a Social Story. Findings included on‐ or above‐standard acceptability in EBP indicators related to important aspects of dependent variables within studies and below‐standard acceptability in indicators related to both internal and external validity of studies.